The Impact of Social Media on Student Academic Performance and Digital Wellbeing - Ilyas Junaid; Munir Hadi Faizan (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
The increasing use of social media among students has raised concerns regarding its impact on academic performance and digital well-being. This study aims to examine the relationship between social media usage, student learning outcomes, and overall well-being in a digital environment. Using a mixed-methods approach, data were collected through surveys and in-depth interviews with high school and university students. The findings indicate that while social media can serve as a valuable tool for academic collaboration and resource-sharing, excessive and unregulated usage often leads to distractions, reduced academic performance, and negative effects on mental health. The study highlights the need for balanced social media engagement and the implementation of digital literacy programs to promote responsible usage. These insights contribute to the ongoing discussion on digital well-being and offer practical recommendations for students, educators, and policymakers.